Can Cinnamaldehyde Increased the Innate Immune System on Medaka Larvae? - Puspitasari, Asthervina Widyastami; Arfiati, Diana; Hu, Shao-Yang (Future Science, 2019)
Fish larvae are the early stage of the life cycle and the key to mass production of fish. Its nature which is susceptible to invade by pathogens, especially viruses, it is an important concern in increasing the innate immune system in virus invading. IFNa and Mx are inducer genes that have the most role in enhancing the innate immune system. The study was conducted in September 2017 with the experimental method. The sample used was 1-day-old medaka larvae in amount 30 fish in each tank with triplicate in each concentration. The cytotoxicity results showed that at 72 hours cinnamaldehyde immersion was 100% of medaka larvae survival rate at a concentration of 2.5 µg mL-1 and 0 µg mL-1 (control). One-Way ANOVA results, the genes expression of IFNa and Mx on 1-day-old medaka larvae showed decreasing at 2.5 µg mL-1 concentration of cinnamaldehyde immersion for 3 days with several observation periods (12h; 24h; 48h; and 72h) compared to control. The lowest expression of IFNa genes was 12h (2.54 x 10-5 ± 6.12 x 10-6) at a 2.5 µg mL-1concentration of cinnamaldehyde, and the highest expression of IFNa gene was 48h (3.95 x 10-4 ± 7.78 x 10-5)at 0 µg mL-1 (control)concentration of cinnamaldehyde. While the lowest Mx gene expression was 72h (8.96 x 10-3 ± 4.51 x 10-4) at a 2.5 µg mL-1concentration of cinnamaldehyde. And the highest Mx gene expression was 72h (0.88 ± 0.26) at 0 µg mL-1 (control)concentration of cinnamaldehyde. The immersion of cinnamaldehyde extract at a concentration of 2.5 µg mL-1 is not able to increase the innate immune system in medaka larvae. More assay is needed to determine the mechanism for the phenomenon of decreasing IFNa and Mx gene expression on fish larvae.